Implementasi Media Permainan Puzzle Dalam Meningkatkan Penguasaan Mufrodat Bahasa Arab Pada Peserta Didik Kelas Iii C Sd Al-Amin Cemani Grogol Sukoharjo Tahun Ajaran 2024/2025 - Tsabita Amanati Mirza (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2025)
This study aims to describe the implementation of puzzle games as a learning medium to improve Arabic vocabulary (mufrodat) mastery among Grade III C students at SD Al-Amin Cemani Grogol, Sukoharjo, in the 2024/2025 academic year. The research was motivated by the low vocabulary mastery among students, which negatively affects their overall Arabic language skills. Using a qualitative approach with a descriptive method, data were collected through observation, interviews, and documentation. The research subjects were the Arabic language teacher and the Grade III C students, while the object of the study was the use of puzzle games as a vocabulary learning tool. The findings reveal that puzzle games enhance student enthusiasm, active participation, and memory retention in learning Arabic vocabulary. Learning activities became more engaging and meaningful, fostering collaborative learning. The media also helped the teacher deliver material more effectively and in varied ways. Thus, puzzle games can serve as an innovative alternative for teaching Arabic vocabulary at the elementary level.